2014
DOI: 10.11648/j.aff.20140301.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Productivity and Technical Efficiency of Cassava Production in Ardo-Kola and Gassol Local Government Areas of Taraba State, Nigeria

Abstract: This study analyzed the productivity and technical efficiency of cassava production in Ardo-Kola and Gassol Local Government Areas of Taraba State. Data were collected from 115 respondents using a structured questionnaire covering 2010/2011 farming season. Inferential statistics were employed in the analysis of data collected. Maximum likelihood estimate (MLE) for all parameters of the stochastic frontier production function and the inefficiency model for the cassava farmers in the study area was employed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
4
11
0
Order By: Relevance
“…These findings are consistent with research by Girei et al (2013), which states that the number of family members increases the level of technical efficiency.…”
Section: Socio-economic Factors Affecting Farmer's Efficiencysupporting
confidence: 92%
“…These findings are consistent with research by Girei et al (2013), which states that the number of family members increases the level of technical efficiency.…”
Section: Socio-economic Factors Affecting Farmer's Efficiencysupporting
confidence: 92%
“…This result shows that majority of the respondents were in their active and productive years. This finding is in agreement with Moyib et al (2013), Girei et al (2014) and Onubuogu et al (2014) that majority of farmers were within the age range of 41-50 years and were still in their active age and may be more receptive to innovation. According to Yusuf, Lategan and Ayindie (2013), age plays a significant role in farming as it determines the farmers' ability to carry out tedious and rigorous work as defined by some activities in okra cultivation.…”
Section: Socio-economic Characteristics Of Okra Farmerssupporting
confidence: 92%
“…The generalized likelihood test gave a value of -915.53 which indicates that the farmers are not fully technically efficient. The findings shares view with the studies of Aboki et al, (2013); Girei et al, (2014); Ogunniyi, (2015); Obike et al, (2016) and Nwike et al, (2017) who reported the technical inefficiencies of cassava farmers at various household levels. Similarly, the result of the stochastic frontier cost function in table 4.13 reveals that all the independent variables gave a positive coefficient.…”
Section: Maximum Likelihood Estimates Of Stochastic Frontier Productisupporting
confidence: 89%